Comparison of oxidative stress status in the kidney tissue of male rats treated with paraquat and nanoparaquat - Fatemeh Bahramibanan; Mohammad Vahabi Rad; Akram Ranjbar; Ashkan Karbasi; Anahita Abbasifard (Scientific Reports)
Abstract The study aimed to compare the oxidative stress status in the kidney tissue of rats treated with paraquat and nanoparaquat. The levels of oxidative stress markers, including malondialdehyde (MDA), total antioxidant capacity (TAC), and thiol groups (TTG), were measured in the kidney tissue samples. A total of forty male Wistar rats were randomly assigned to eight groups, each consisting of five rats: a control group, a paraquat (PQ) group, an N-acetylcysteine (NAC) group, groups receiving nanoparaquat α and β (α and β), groups receiving PQ and NAC (PQ + NAC), and groups receiving nanoparaquat α and β with NAC (+ NACα and β). Paraquat, a widely used herbicide, induces severe oxidative damage in kidneys through radical formation and cellular stress. Newly developed nanoparaquat formulations may modify its toxicity profile and tissue distribution patterns. The results revealed that rats treated with paraquat showed a significant increase in Lipid Peroxidation Oxidation (LPO) levels compared to the control group and those treated with NAC. However, treatment with nanoparaquat α and β resulted in a decrease in LPO levels compared to the paraquat-treated group. Additionally, when nanoparaquat α and β were administered in combination with NAC, a further reduction in LPO levels was observed compared to the PQ treated group. Regarding TAC levels, the PQ group exhibited a significant decrease compared to the control group and the NAC-treated group. However, treatment with nanoparaquat β resulted in higher TAC levels compared to the PQ group. Moreover, when nanoparaquat α and β were administered in combination with NAC, there was an increase in TAC levels compared to the PQ group. In terms of TTG levels, the PQ group showed a significant decrease compared to the control group and the NAC group. However, treatment with nanoparaquat β led to an increase in TTG levels compared to the PQ group. Furthermore, when nanoparaquat α and β were administered in combination with NAC, there was an increase in TTG levels compared to the PQ group. Overall, the results suggest that treatment with nanoparaquat, especially nanoparaquat β, may have a protective effect against oxidative stress induced by PQ toxicity in the kidney tissue of rats. Further studies are warranted to elucidate the underlying mechanisms and potential therapeutic implications of nanoparaquat in oxidative stress-related kidney disorders.